A taxonomic summary and revision of Rozella (Cryptomycota) - Peter M. Letcher; Martha J. Powell (IMA Fungus)
Abstract Rozella is a genus of endoparasites of a broad range of hosts. Most species are known by their morphology and host specificity, while only three have been examined ultrastructurally and had portions of their genome sequenced. Determined in molecular phylogenies to be the earliest diverging lineage in kingdom Fungi, Rozella currently nests among an abundance of environmental sequences in phylum Cryptomycota, superphylum Opisthosporidia. Here we briefly summarize a history of Rozella, provide descriptions of all species, and include a key to the species of Rozella.